Role of air pollution by particulate matter in the pathogenesis of cardiovascular diseases. Prevention measures - A. F. Kolpakova; R. N. Sharipov; O. A. Volkova; F. A. Kolpakov (Кардиоваскулярная терапия и профилактика)
The review highlights contemporary concepts about the role of atmospheric air pollution by particulate matter (PM) in pathogenesis of cardiovascular diseases (CVD). We used publications from the PubMed and Russian Science Citation Index databases. The influence of PM on the development and progression of CVD is considered depending on size, origin, chemical composition, concentration in air. PM with an aerodynamic diameter of ≤2,5 μm (PM2,5) are recognized as the most dangerous. Epidemiological studies have established a dose-dependent effect PM. Oxidative stress, damage of genome of cell and epigenetic changes associated with PM effect are the important component of CVD pathogenesis. Systematization of scientific data through a formalized description helps to understand the pathogenesis of CVD and facilitates its practical use for assessing the risk of occurrence, early diagnosing, prognostication, increasing the effectiveness of treatment, and developing preventive measures.